Outcome measures after anterior cervical decompression and fusion surgery –non-respondents do not bias the results: A Finnish spine register (FinSpine) study - N. Klimko; N. Danner; H. Salo; A. Malmivaara; V. Leinonen; J. Huttunen (Brain and Spine)
Introduction: Comprehensive national spine registers are used in the Nordic countries. Register data is inherently incomplete, raising concerns about the derived results due to non-respondent bias. Few studies have addressed the effect of non-respondents on the integrity of patient-reported outcome data in national spine registers, suggesting that outcome measures after spine surgery may not differ between respondents and non-respondents. Research question: Using the Finnish national spine register (FinSpine), we aimed to assess whether non-respondents would bias patient-reported outcomes at 12 months following anterior cervical decompression and fusion (ACDF) surgery. Material and methods: FinSpine data from 5563 ACDF surgeries since 2016 were analyzed, supplemented with prescription records from the Finnish Social Insurance Institution and subcohort data from Kuopio University Hospital. Patients were grouped based on whether they completed post-operative outcome surveys. Outcomes were compared on neck and upper extremity pain, functional capacity, quality of life, sleep quality, return to work, regular use of pain medication, and opioid purchases 12 months after surgery. Results: Out of 5563 ACDF patients, 1362 (24.5%) purchased opioids during the first post-operative year. There were no significant differences in the mean cumulative opioid purchases between respondents and non-respondents. In the subcohort (n = 60), all non-respondents (n = 29) were reached and interviewed. There were no differences between respondents and non-respondents in any outcome measures at 12 months. Discussion and conclusion: Non-respondents do not bias the assessment of outcome measures following ACDF at 12 months, supporting the validity and reliability of national quality registers like FinSpine for clinical research.